Monitoring conformational heterogeneity of the lid of DnaK substrate‐binding domain during its chaperone cycle. (4th July 2016) - Banerjee, Rupa; Jayaraj, Gopal Gunanathan; Peter, Joshua Jebakumar; Kumar, Vignesh; Mapa, Koyeli
Abstract : DnaK or Hsp70 of Escherichia coli is a master regulator of the bacterial proteostasis network. Allosteric communication between the two functional domains of DnaK, the N‐terminal nucleotide‐binding domain (NBD) and the C‐terminal substrate‐ or peptide‐binding domain (SBD) regulate its activity. X‐ray crystallography and NMR studies have provided snapshots of distinct conformations of Hsp70 proteins in various physiological states; however, the conformational heterogeneity and dynamics of allostery‐driven Hsp70 activity remains underexplored. In this work, we employed single‐molecule Förster resonance energy transfer (sm‐FRET) measurements to capture distinct intradomain conformational states of a region within the DnaK‐SBD known as the lid. Our data conclusively demonstrate prominent conformational heterogeneity of the DnaK lid in ADP‐bound states; in contrast, the ATP‐bound open conformations are homogeneous. Interestingly, a nonhydrolysable ATP analogue, AMP‐PNP, imparts heterogeneity to the lid conformations mimicking the ADP‐bound state. The cochaperone DnaJ confers ADP‐like heterogeneous lid conformations to DnaK, although the presence of the cochaperone accelerates the substrate‐binding rate by a hitherto unknown mechanism. Irrespective of the presence of DnaJ, binding of a peptide substrate to the DnaK‐SBD leads to prominent lid closure. Lid closure is only partial upon binding to molten globule‐like authentic cellular substrates, probably to accommodate non‐native substrate proteins of varied structures. Abstract : DnaK or E. coli Hsp70 was subjected to single‐molecule Förster resonance energy transfer (sm‐FRET) measurements to capture distinct conformational states of the lid of its substrate‐binding domain. We demonstrate that the lid of the chaperone adopts characteristics conformational states in the presence of nucleotides, J‐domain cochaperone and different cellular substrates explaining finer details of DnaK chaperone function.